Inverse size-dependent Stokes shift in strongly quantum confined CsPbBr3 perovskite nanoplates. Issue 46 (15th November 2022) - Vurgaft, Amit; Strassberg, Rotem; Shechter, Reut; Lifer, Rachel; Dahl, Jakob C.; Chan, Emory M.; Bekenstein, Yehonadav
Abstract : We observe that different growth conditions and resulting morphologies of CsPbBr3 nanocrystals yield opposite stokes shift size-dependent trends. This emphasizes the different photo-physics for quantum-confined nanoplate and nanocube morphologies. Abstract : Colloidal semiconductor nanocrystals (NCs) are used as bright chromatic fluorophores for energy-efficient displays. We focus here on the size-dependent Stokes shift for CsPbBr3 nanocrystals. The Stokes shift, i.e., the difference between the wavelengths of absorption and emission maxima, is crucial for display application, as it controls the degree to which light is reabsorbed by the emitting material reducing the energetic efficiency. One major impediment to the industrial adoption of NCs is that slight deviations in manufacturing conditions may result in a wide dispersion of the product's properties. A data-driven analysis of over 2000 reactions comparing two data sets, one produced via standard colloidal synthesis and the other via high-throughput automated synthesis is discussed. We show that differences in the reaction conditions of colloidal CsPbBr3 nanocrystals yield nanocrystals with opposite Stokes shift size-dependent trends. These match the morphologies of two-dimensional nanoplatelets (NPLs) and nanocrystal cubes. The Stokes shift size dependence trend of NPLs and nanocubes is non-monotonic indicating different physics is at play for the two nanocrystal morphologies. For nanocrystals with cubic shape, with the increase of edge length, there is a significant decrease in Stokes shift values. However, for NPLs with the increase of thickness (1–4 ML), Stokes shift values will increase. The study emphasizes the transition from a spectroscopic point of view and relates the two Stokes shift trends to 2D and 0D exciton dimensionalities for the two morphologies. Our findings highlight the importance of CsPbBr3 nanocrystal morphology for Stokes shift prediction.